Assessment of water ecological health in shallow lakes: A new framework based on water resource-environment-ecology - Yanru Tao; Qiujin Xu; Mingke Luo; Wenjing Dong; Yan Pang (Ecological Indicators)
In lake ecosystems, human disturbances can severely damage ecological integrity, particularly in shallow lakes. Existing research on water ecological health (WEH) assessment has often overlooked critical aspects such as water resources, water environment, and water ecology, which makes the previous research methods less effective. Therefore, it is essential to explore a new framework for addressing the challenges of WEH assessment in shallow lakes. In this study, Taihu Lake in China between 2011 and 2023 was used as a case study. This paper first constructed a new framework based on water resource-environment-ecology (WREE), which includes seven key indices, and the reasons for this change were explored. Additionally, the eutrophication assessment and the Pressure-State-Response (PSR) evaluation method were employed to assess the effectiveness of this new approach framework. The results show that the water quality in Taihu Lake improved to a certain extent from 2011 − 2023, whereas eutrophication and cyanobacterial blooms have not significantly improved, and WEH has been classified into the medium state (level III). In particular, the WEH values were relatively low in 2013 and 2017, and showed a fluctuating downward trend from 2020 to 2023, which may be attributed to meteorological factors and human activities leading to an increase in pollution-tolerant species and a decrease in biodiversity, ultimately resulting in a deterioration of WEH. The long-term WEH assessment results for Taihu Lake highlight the applicability of the framework based on the WREE, and can be widely applied to similar lake ecosystems but are not applicable to short-term seasonal variations. Given the impacts of increased human activities and climate change, the WREE framework provides valuable insights for the sustainable development and effective management of lake ecosystems, while also enhancing the existing WEH assessment theory.